Isometry of potential suture attachment sites for the cranial cruciate ligament deficient canine stifle - Roe, S. C.; Kue, J.; Gemma, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
For a suture that spans a joint to provide support without limiting range of motion, its attachment points on either side of the joint must remain the same distance from each other from full extension to full flexion. The effect of location of the tibial crest attachment for a fabello- tibial crest suture was studied in seven canine cadaveric stifles. The distance from a fabella marker to each of 11 tibial markers was determined from radiographs of each limb, as it progressed from 150° to 130°, 105°, 90°, 65° and 45° of flexion. The marker locations that were more proximal and cranial on the tibial crest had the least percent change in distance. The effect of anchoring the suture to the femur at a site other than the fabella was investigated using the same radiographs. Five marks were placed in a grid on the caudal portion of the femoral condyle and supracondylar region. The mean percent change in length from each femoral point to the five more proximal and cranial tibial markers was determined. The least change in length occurred for those femoral points located close to the origin of the cranial cruciate ligament. Locations more proximal or cranial resulted in large changes in length, particularly when matched with less ideal tibial locations. Although this study does not directly examine length changes in sutures, it demonstrates that there are some locations for the origin and insertion of an extracapsular suture that are associated with less length change than others, and also forms the basis for future investigations.
Keywords: Canine cranial cruciate ligament; extracapsular suture; length; isometry